Oxidative stress in multiple sclerosis—Emerging imaging techniques - Hollen, Christopher; Neilson, Lee E.; Barajas, Ramon F.; Greenhouse, Ian; Spain, Rebecca I. (Frontiers in Neurology, 2023)
While conventional magnetic resonance imaging (MRI) is central to the evaluation of patients with multiple sclerosis, its role in detecting the pathophysiology underlying neurodegeneration is more limited. One of the common outcome measures for progressive multiple sclerosis trials, atrophy on brain MRI, is non-specific and reflects end-stage changes after considerable neurodegeneration has occurred. Identifying biomarkers that identify processes underlying neurodegeneration before it is irreversible and that reflect relevant neurodegenerative pathophysiology is an area of significant need. Accumulating evidence suggests that oxidative stress plays a major role in the pathogenesis of multiple neurodegenerative diseases, including multiple sclerosis. Imaging markers related to inflammation, myelination, and neuronal integrity have been areas of advancement in recent years but oxidative stress has remained an area of unrealized potential. In this article we will begin by reviewing the role of oxidative stress in the pathogenesis of multiple sclerosis. Chronic inflammation appears to be directly related to the increased production of reactive oxygen species and the effects of subsequent oxidative stress appear to be amplified by aging and accumulating disease. We will then discuss techniques in development used in the assessment of MS as well as other models of neurodegenerative disease in which oxidative stress is implicated. Multiple blood and CSF markers of oxidative stress have been evaluated in subjects with MS, but non-invasive imaging offers major upside in that it provides real-time assessment within the brain.